Cloning and characterization of the major outer membrane protein gene (ompH) of Pasteurella multocida X-73. - Luo, Y (1997)
The major outer membrane protein (OmpH) of Pasteurella multocida X-73 was purified by selective extraction with detergents, followed by size exclusion chromatography. The planar lipid bilayer assay showed that OmpH has pore-forming function. The average single channel conductance in 1.0 M KCl was 0.62 nS. The gene (ompH) encoding OmpH has been isolated and sequenced by construction of a genomic library and PCR techniques. The coding region of this gene is 1,059 bp long. The predicted primary protein is composed of 353 amino acids, with a 20-amino-acid signal peptide. The mature protein is composed of 333 amino acids with a molecular mass of 36.665 kDa. The ompH gene encoding mature protein has been expressed in Escherichia coli by using a regulatable expression system. The ompH gene was distributed among 15 P. multocida serotypes and strain CU. Protection studies showed that OmpH was able to induce homologous protection in chickens. These findings demonstrate that OmpH is a protective outer membrane porin of strain X-73 and is conserved among P. multocida somatic serotypes.